Using Online Assessments in the Age of Covid-19: An Exploratory Study of Cognitive Load in Higher-Education Teachers - Karunaweera, Anushka (Université d'Ottawa / University of Ottawa, 2023)
Cognitive load is based on the principle that working memory is limited in its capacity to hold and store information. The demands of assessment on teachers; designing, implementing, and providing feedback to students, may create a strain on working memory. With the onset of the Covid-19 pandemic, post-secondary systems world-wide shifted teaching, learning and assessments to online platforms. Considering the sudden shift from in-person to online modes, this paper explores cognitive load in higher-education teachers who use online assessment in a pandemic context, to answer two research questions; What is the process of using online assessment among higher-education teachers? How does this process influence cognitive load? The study uses a case study approach to explore cognitive load in teachers, wherein the major case is higher-education assessment during the Covid-19 institutional closures, with each participant presenting a unique instance of the case. The study included a heterogenous sample of six post-secondary level teachers (n = 6) from a public university in Canada and used an online questionnaire, assessment artefacts and a semi-structured interview to address the two research questions proposed. The findings of this paper show the process of using online assessment as including experiences that tied to affect, moments that required support and moments that were high and/or low in terms of workload. There may not be a unidirectional influence on cognitive load. Rather, the load may also influence the process, potentially suggesting a relationship between the two that could build on each other until sufficient mental resources are acquired to address the load. The findings ultimately support the conclusion that regardless of new technologies or new features, cognitive resources were still potentially exhausted with how to use the technologies rather than what technologies were available to use.
Keywords: Educational Technologies; Online Assessment; Higher-Education; Cognitive Load